The interaction of technological innovation and increases in productive capacity: Multiplication of loaves and fishes? - M. Guisado-González; M. Guisado-Tato; C. Ferro-Soto (South African Journal of Business Management, 2016)
Using the experience curve as a basis, this study analyses the influence of technology and increases to productive capacity on business productivity. In addition, we tested if both variables are complementary. The data used comes from the Business Environment and Enterprise Performance Survey (BEEPS), which refers to the Spanish economy in 2005. Our findings reveal that radical innovation activities and increases in productive capacity have a significant positive impact on business productivity. Incremental innovations do not have a significant influence, while the incorporation of technology through the purchase of machinery and equipment has a negative and significant influence. Finally, the conducted tests reveal that the different kinds of technologies analysed and increases in productive capacity are not complementary variables.
Keywords: 650